The participation of the professional women of the Orient University. Their access to management charges (Encuentros, 2016)
The objective of this article is to study the participation of professional women from Orient University and their access to management charges, specifying the gender inequities manifest themselves in this process. The first of those results was on the quantitative characterization of the women presence in the different teaching and scientific categories, knowledge areas and others stratums, as well as in the different levels of management charges. By the other hand, we had evaluated the conditions which has influence on the quality of the management women's duties, attended to work’s conditions and the patriarchal’s conditions of gender where they would be apply.Keywords: genders, empowerment, university.